Cúspide em garra: relato de caso - Paulon, Samuel Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cusp claw is an anomaly that occurs most commonly on the upper incisors, presenting itself as a well-defined accessory cusp that extends from the cementum-enamel junction or the cingulate region, moving toward the incisal face, compromising the affected tooth times to alter the natural occlusion of the same. When this anomaly undertakes occlusion, careful clinical examination / x-ray should be performed in order to establish the plan tr4atamento. This anomaly can be associated with Rubinstein-Taybi syndrome. This paper reports a case of cusp claw in a patient 07 years of age, showing signs of Global Delay DNPM, hyperactive, with mild disabilities and learning difficulties, and etiology of neonatal hypoxia was referred to CIOS - Service Centre dental to the Person with Disabilities, Faculty of Dentistry of Araçatuba-UNESP. On clinical examination it was observed that the tooth 21 had a claw cusp on the buccal and lingual. The periapical radiograph did not provide sufficient data to support the diagnosis. Was then appointed the examination by computed tomography (Cone Beam) which contributed greatly to defining the limits of accessory cusps, suggesting no pulp involvement. Because of this, the cusps were worn and some areas received aesthetic composite resin restorations

Cúspide em garra é uma anomalia que ocorre mais comumente nos incisivos superiores, apresentando-se como uma cúspide acessória bem definida que se estende a partir da junção cemento-esmalte ou da região do cíngulo, seguindo em direção à face incisal, comprometendo o dente afetado à vezes alterando a oclusão natural do mesmo. Quando esta anomalia compromete a oclusão, criterioso exame clínico/radiográfico deverá ser realizado para que se estabeleça o plano de tr4atamento. Esta anomalia pode estar relacionada com a Síndrome de Rubinstein-Taybi. Este trabalho relata um caso de cúspide em garra em um paciente de 07 anos de idade, apresentando quadro de Retardo Global no DNPM, hiperativo, com deficiência leve e dificuldade de aprendizagem, com etiologia de hipóxia neonatal, foi encaminhado ao CAOE - Centro de Assistência Odontológica à Pessoa com Deficiência, da Faculdade de Odontologia de Araçatuba-UNESP. Ao exame clínico observou-se que o dente 21 apresentava uma cúspide em garra na face vestibular e palatina. A radiografia periapical não forneceu dados suficientes para auxiliar o diagnóstico. Foi então indicado o exame por tomografia computadorizada (Cone Beam) que contribuiu sobremaneira para a definição dos limites das cúspides acessórias, sugerindo o não comprometimento pulpar. Em razão disto, as cúspides foram desgastadas e algumas áreas receberam restaurações estéticas com resina composta
Keywords: Síndrome de Rubinstein-Taybi; Dente canino; Anormalidades dentárias; Rubinstein-Taybi Syndrome